The Atlantic Salmon Gill Transcriptome Response in a Natural Outbreak of Salmon Gill Pox Virus Infection Reveals New Biomarkers of Gill Pathology and Suppression of Mucosal Defense - Gjessing, Mona C.; Krasnov, Aleksei; Timmerhaus, Gerrit; Brun, Svante; Afanasyev, Sergey; Dale, Ole Bendik; Dahle, Maria K. (Frontiers in Immunology, 2020)
The salmon gill poxvirus (SGPV) is a large DNA virus that infects gill epithelial cells in Atlantic salmon and is associated with acute high mortality disease outbreaks in aquaculture. The pathological effects of SGPV infection include gill epithelial apoptosis in the acute phase of the disease and hyperplasia of gill epithelial cells in surviving fish, causing damage to the gill respiratory surface. In this study, we sampled gills from Atlantic salmon presmolts during a natural outbreak of SGPV disease. Samples covered the early phase of infection, the acute mortality phase, the resolving phase of the disease and control fish from the same group and facility. Mortality, the presence and level of SGPV and gill epithelial apoptosis were clearly associated. The gene expression pattern in the acute phase of SGPV disease (SGPVD) was in tune with the pathological findings and revealed novel transcript-based disease biomarkers, including pro-apoptotic and proliferative genes, along with changes in expression of ion channels and mucins. The innate antiviral response was strongly upregulated in infected gills and chemokine expression was altered. The regenerating phase did not reveal adaptive immune activity within the study period, but several immune effector genes involved in mucosal protection were downregulated into the late phase, indicating that SGPV infection could compromise mucosal defense. These data provide novel insight into the infection mechanisms and host interaction of SGPV.